Economic valuation of climate induced losses to aquaculture for evaluating climate information services in Bangladesh - Islam, Shammunul; Hossain, Peerzadi; Braun, Melody; Amjath-Babu, Tharayil Shereef; Mohammed, Essam Yassin; Krupnik, Timothy; Chowdhury, Anwar Hossain; Thomas, Mitchell; Mauerman, Max (Elsevier, 2024)
Very little research has focused on climate impacts on aquaculture and the potential of climate information services (CIS) for aquaculture to support sustainable development goals 2030 (SDGs).1 This study represents an effort to bridge this gap by conducting a first ex-ante economic evaluation of CIS for aquaculture in Bangladesh by semi-automating the extraction of data on climate-induced fish losses during 2011 to 2021 from popular online newspaper articles and corroborating them with available government and satellite datasets. During this period, Bangladesh faced an estimated loss of around 140 million USD for hatcheries, open water fish and shrimp. When validated with a year of country-wide official data on climate-induced economic losses to aquaculture, the damage reported from these media sources is approximately 10 percent of actual losses. Given this rule of thumb, the potential economic value of aquacultural CIS could be up to USD14 million a year, if 10 percent of the damage can be offset by appropriate services through a range of multi-sector efforts to establish and extend these services to farmers at scale.